Implementasi Metode Penilaian Bangunan Hijau Berbasis Aplikasi EDGE pada Pembelajaran Arsitektur - Christian Nindyaputra Octarino; Yordan Kristanto Dewangga (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Implementation of Green Building Assessment Method based on EDGE Application in Architecture Study The climate change phenomenon in the modern era is one of the leading causes of environmental quality degradation. The building and construction sector is the largest contributor to carbon emissions, reaching 40% compared to other sectors. The sustainability of life will continue to be threatened by developments that are not ecologically friendly. Thus, humans must exercise greater responsibility in all of their development decisions. It is essential to inculcate early knowledge of sustainability and green building concepts, especially in architectural education. The EDGE (Excellence in Design for Greater Efficiencies) application is considered capable of being a tool in the design process that can practically calculate the impact of each design element on building efficiency. This study aims to evaluate the implementation of a green building assessment method based on the EDGE application in the learning process of architecture students. The output of the study was the skill to design a building with a green building approach using EDGE as a tool to quantify the building's performance. Based on the output and survey of participating students, they all stated that using EDGE was very useful in the architectural design process. More than 80% also mentioned that the workshop method used in the class was effective. Through this learning process, the fundamental principles of green building design are accessible to students and can be included in architectural plans.